PENERAPAN METODE KONTEKSTUAL INVESTIGASI BISNIS DAN GAME ULAR TANGGA KOMBI DALAM UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR KOMUNIKASI BISNIS (Fakultas Ekonomi, Universitas Negeri Semarang, 2012)
The objective of this study is to improve students’ activity and students’ learning outcomes for accounting students in the first grade in SMK Negeri 1 Salatiga at second semester in the academic year of 2011/2012. This study was a class action research which was designed into two main cycles. Each cycle consisted of four stages started from planning, acting, observing and reflecting. The result showed that : (1) Learning activities with the above three criteria, increase from 33.34% before the cycle, 66.66% in the first cycle and 93.44% in the second cycle, (2) The learning outcomes increase from 22.22% before the cycle, 75% in the first cycle and 94.44% in the second cycle. Therefore; the use of this method could be a teachers’ reference in implementing the teaching-learning process.